2015
DOI: 10.1002/crat.201500044
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of kesterite nanopowders with bandgap tuning ligands

Abstract: A rapid development of solar cells has been observed within recent years. Semiconducting materials based on Cu 2 ZnSnS 4 with the kesterite structure offer a promise of low-cost and environmentally friendly solar cells. The energy gap of Cu 2 ZnSnS 4 , which is about 1.5 eV, can be optimized with addition of organic ligands. We report a method of obtaining kesterite nanopowders with grain diameter of approximately 5 nm via solution synthesis using metal chlorides and sulfur in oleylamine at 230°C. The ligand e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 15 publications
1
3
0
Order By: Relevance
“…The presence of excess Cu comes from the fluorescent signal, which is created by/due to the supporting copper grid. The results confirmed the stoichiometry of the nanopowders as Cu2ZnSnS4 [37][38][39].…”
Section: Resultssupporting
confidence: 87%
See 1 more Smart Citation
“…The presence of excess Cu comes from the fluorescent signal, which is created by/due to the supporting copper grid. The results confirmed the stoichiometry of the nanopowders as Cu2ZnSnS4 [37][38][39].…”
Section: Resultssupporting
confidence: 87%
“…The three characteristic reflexes of kesterite (2θ = 28.530, 47.329, and 56.175 degrees) are clearly visible. The fourth one (2θ =32.988 degree) is noticeable in the patterns from which it can be concluded that nanocrystals of kesterite were obtained [38][39][40]. Calculations based on the Scherrer method and FWHM confirms that the grain size is 5 nm [41].…”
Section: Resultsmentioning
confidence: 57%
“…The E g of the solid solution has the advantage of matching the energy corresponding to the maximum efficiency in the Shockley-Queisser plot for a single absorber cell [15]. The tunability of the E g of the material from 1.5 to 2.1 eV makes it suitable for constituent-element substitutions [16,17]. This makes the material suitablefor use as the uppermost component in tandem multijunction solar cell when substituted with elements such as silver (Ag) and germanium (Ge) [18,19].…”
Section: Introductionmentioning
confidence: 99%
“…Theoretical and experimental investigations of monolayers, nanoparticles, surfaces, and clusters of distinct chemical compounds reveal the possibility of bandgap tuning via functionalization with ligands, such as chromophores or conjugated organic groups [38][39][40][41]. Synthesis of a nanopowder with a bandgap tuning ligand was demonstrated (for example) in the case of a high-temperature reaction in a solvent, but there are no reports on such an approach in sonochemical synthesis [42]. This is probably because it may yet be hampered by the possible modification or even destruction of molecules of organic ligands by radicals generated in the reaction medium as a result of the action of ultrasound radiation (e.g., water sonolysis) [43,44].…”
Section: Introductionmentioning
confidence: 99%